Consistency between the geographic distributions of overweight and obesity among children and adults in China - Yudan Liu; Hui Fan (BMC Public Health)
Abstract Background Childhood obesity is associated with obesity in adulthood, but the consistency between the geographic distributions of obesity among children and adults in China is not fully understood. We aimed to examine the consistency of the geographic distributions of overweight and obesity between adults and children in China. Methods This was a cross-sectional study including 11,940 adults. Data were from the China Health and Nutrition Survey conducted in 2015. Body mass index (BMI) and waist circumference (WC) were measured. The geographical areas were categorized as low-, middle- or high-epidemic areas according to the prevalence of overweight and obesity in children at the provincial level, based on the classification system determined by the National Health Commission. We examined the differences in adult BMI, WC, prevalence of overweight and obesity, abdominal overweight and obesity across the three classification areas. Results In this study, the overall prevalence of overweight/obesity and abdominal overweight/obesity were 49.8% and 61.0% respectively. We observed the prevalence of overweight and obesity among adults increased from low- to middle- and high- epidemic areas. Compared with adults from low-epidemic areas, those from middle- and high-epidemic areas had a higher odds of having overweight or obesity (odds ratio [95% confidence interval]: 1.518 [1.362, 1.692] and 2.190 [1.972, 2.433], respectively). Similar results were observed for abdominal overweight and obesity in adults. Conclusion Our study confirmed the consistency in the geographical clustering of overweight and obesity among adults and children, which suggests that interventions addressing overweight and obesity should be targeted at both local children and adults simultaneously.